Application of Islam Ruhama Junior High School Library Administration Using Visual Basic 6.0 - Yulia Surya Kurnia Wati (Jurnal Sistem Informasi, 2010)
In this paper the author tries to help the library at  Islam Ruhama Junior High School in making lending services, data storage  books, and members can also view the report, by making an application data  base. Apliksi is expected to accelerate the service and reduce use of paper. Data storage - data is stored using hard disk media  as a storage file so the use of less paper so it does not require more storage space and can find data quickly and  efficient as well as recording transactio ns peminjman. Statements in this application can display the data -data required like all of the data book, data members, and transactions - borrowing transaction. With This report is expected to provide accurate and timely information for  library board.